Research on the Interaction Mechanism Between α Mino-Phosphonate Derivative Q-R and Harpin-Binding Protein 1 in Tobacco (Nicotiana tabacum) Plants - Huang, Maoxi; Yan, Yunlong; Wang, Li; Chen, Jun; Liu, Tao; Xie, Xin; Li, Xiangyang (Frontiers in Microbiology, 2021)
Amino-phosphonate derivative R-diphenyl-1-(4-methylbenzothiazole-2-amino)-1-(thiphene-2-yl)-methylphosphonate (Q-R) has a high protective anti-tobacco mosaic virus (TMV) activity. However, the mechanism responsible for Q-R’s effect on TMV infection is largely unknown. Here, we studied the expression levels of harpin-binding protein 1 (HrBP1) and pathogenesis-related protein-1a (PR-1a) in TMV-infected tobacco plants by using reverse transcription quantitative real-time PCR. Then, we verified the interactions between Q-R and the HrBP1 protein from Escherichia coli using isothermal titration calorimetry and studied the Q-R-associated assembly of HrBP1 using size-exclusion chromatography. The results showed that the expression levels of HrBP1 and PR-1a genes were significantly increased by Q-R at the transcriptional level in TMV-infected tobacco plants, and the E. coli-expressed HrBP1 protein was assembled into oligomers by Q-R via binding to HrBP1 with a dissociation constant of 1.19 μΜ. We, therefore, concluded that Q-R activated the HrBP1 and PR-1a genes and enhanced the ability of HrBP1 to assemble in tobacco plants.